Motivasi Belajar Auditing Ditinjau Dari Penggunaan Internet Sebagai Media Belajar Dan Lingkungan Kampus Pada Mahasiswa Pendidikan Akuntansi Angkatan 2013 - Putri Anggraini, Dessy; , Dr.Suyatmini,SE.,M.Si (2017)
The objective of this study was to determine: 1) the effect of the use of the internet as a media of learning on Auditing learning motivation, 2) The environmental influences concerning in learning Auditing motivation, and 3) the effect of the use of the Internet as a media of learning and campus environment on Auditing learning motivation. The method was used in this research was quantitative associative approach by using statistical method to make the conclusion. This study took subject on Accounting Education students, VII semester 2013 generation who took a course on Auditing in academic year 2016/2017. The population in this research were 127 students with sample 97 students were taken by proportional random sampling technique by lottery. The technique of collecting the data was used questionnaires that have been tested previously using validity test and reliability test. The technique of analysis the data was used regression multiple linear analysis. The results of the regression analysis was obtained equation regression: Y = 7,437 + 0,113X1 + 0,714X2, which meant Auditing learning motivation in students affected by the use of the internet as a media of learning and campus environment. Based on the analysis and discussion can be concluded that: 1) the use of the internet as a media of learning had a significant effect on Auditing learning motivation. It was proven from the regression analysis were obtained t count > t table that was 2.506 > 1.986 with significance value < 0.05, that was 0.001. 2) The campus environment significantly influenced in auditing learning motivation. It was proven from the regression analysis were obtained t count > t table that was 2.022 > 1.986 with significance value < 0.05, that was 0.000. 3) The use of the Internet as a media of learning and campus environment simultaneously gave significant effect on Auditing learning motivation. It was proven from the regression analysis which obtained from F count > F table that was 53.613 > 3.093 with significance value < 0.05 was 0.000. 4) The variable of the use of the internet as a media of learning and campus environment gave big influence simultaneously in amount 53.3%, while 46.7% was influenced by other variable which not examined in this research